PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI DAN KUALITAS LAYANAN TERHADAP KEPUASAN PEMANFAAT APLIKASI SRIKANDI DI WILAYAH PEMERINTAH KABUPATEN MUSI RAWAS - Hairani, Puspa; Hariani, Puspa; Alexsander, Alexsander; Aprianty, Henny (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2025)
This study aims to analyze the influence of system quality, information quality, and service quality on user satisfaction with the Srikandi application within the Musi Rawas Regency Government. A quantitative research method was employed using a survey technique with questionnaires. The sample consisted of 100 civil servants (ASN) who use the Srikandi application across various local government agencies (OPDs). Data were analyzed using multiple linear regression. The results indicate that, partially, system quality (t = 7.666; p < 0.05), information quality (t = 9.560; p < 0.05), and service quality (t = 5.312; p < 0.05) have a significant positive effect on user satisfaction. Simultaneously, all three variables significantly influence user satisfaction (F = 67.106; p < 0.05). This study underscores the importance of improving system, information, and service quality to enhance user satisfaction with digital applications in the public sector.